2018
DOI: 10.1007/s11926-018-0744-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Axial Spondyloarthritis: Women Are Not So Lucky

Abstract: Purpose of ReviewAnkylosing spondylitis (AS) was historically seen as a predominantly male disease. However, more recent data showed a more homogenous sex prevalence. Unfortunately, in many studies in axial spondyloarthritis (axSpA), the number of women included is low and the analyses are often not stratified for gender distribution. The purpose of this review is to aggregate the existing data on gender differences in axSpA in order to increase the awareness that female axSpA patients are still under-recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
171
3
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 81 publications
19
171
3
9
Order By: Relevance
“…In addition, female gender was found to experience more improvement in BASDAI and BASFI, which was consistent with the result from a national prospective observational study in the United Kingdom . However, in contrast, most other observational studies suggested that female gender was associated with a significantly lower response . The major difference between our analysis and those observational studies is that our identification of covariate is based on the relative drug effects, which may show different results from that based on the absolute treatment effects .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In addition, female gender was found to experience more improvement in BASDAI and BASFI, which was consistent with the result from a national prospective observational study in the United Kingdom . However, in contrast, most other observational studies suggested that female gender was associated with a significantly lower response . The major difference between our analysis and those observational studies is that our identification of covariate is based on the relative drug effects, which may show different results from that based on the absolute treatment effects .…”
Section: Discussionsupporting
confidence: 86%
“…a dilemma, and randomized clinical trials that are generated for examining the difference between genders may be required. 23 Compared with the conclusions of previous meta-analyses, this study provided different and more detailed rank-order. The detailed comparison of outcomes is listed in Table S1.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Thus, early classification criteria that focus primarily on axial symptoms would be less likely to identify female patients with axSpA. The adoption of a broader definition of axSpA that includes peripheral features has revealed that the prevalence of axSpA may be nearly equal between men and women [31,79,80] and that nonradiographic axSpA may be more common in women than men [81]. Based on the available literature, there is limited information on the impact of delayed diagnosis in women or patients with nonradiographic axSpA.…”
Section: Discussionmentioning
confidence: 99%